Triumph der Mitte - Oppermann, Matthias (2020)
Despite the opposition of two parties - first the Whigs and the Tories, then the Liberals and the Conservatives - 19th century Britain was characterized by a political culture of moderation. The bearers of this political culture were a group of politicians who always sought the middle way between the extremes and were known as Liberal Tories or Liberal Conservatives. This book fills a research gap by examining the development of this British Liberal Conservatism in the period from 1750 to 1850, first looking at Edmund Burke's political philosophy and then showing how the Liberal Tories and Liberal Conservatives who followed him drew on his thinking. It shows how politicians such as George Canning and Sir Robert Peel, based on Burke and the political philosophy of the "Old Whigs", pursued a centrist policy that was always oriented towards the virtues of moderation and prudence. The book thus sheds light on the conservative variant of liberalism that characterized Great Britain throughout the 19th century.